The Influence of Workload and Motivation on Employee Performance through Job Satisfaction - Souisa, Novita; Macpal, Stelly Julia; Biay, Agustinus (Indonesian Journal Economic Review (IJER), 2025)
This study examines the impact of workload and motivation on employee Performance through job satisfaction. Employee Performance plays a crucial role in achieving organizational goals. Excessive workload can lead to stress and decrease job satisfaction, while high motivation can enhance employees' dedication and enthusiasm in performing their tasks. This research adopts a quantitative approach with a sample of 190 employees from government institutions in Indonesia. Data were collected using questionnaires with a Likert scale to measure the variables of workload, motivation, job satisfaction, and Performance. The results of the analysis show that workload negatively affects job satisfaction, which, in turn, impacts Performance. Motivation was found to positively influence Performance, with job satisfaction as a mediator linking motivation and Performance. These findings indicate that effective workload management and a supportive environment are crucial in maintaining employee motivation and job satisfaction, ultimately improving their Performance. While this study's model explains a significant portion of the variation in job satisfaction and employee Performance, other factors influencing Performance may not have been identified in this research.